2015
DOI: 10.1007/s40429-015-0053-z
|View full text |Cite
|
Sign up to set email alerts
|

On the Development of Implicit and Control Processes in Relation to Substance Use in Adolescence

Abstract: Adolescence is a period in which brain structures involved in motivation and cognitive control continue to develop and also a period in which many youth begin substance use. Dual-process models propose that, among substance users, implicit or automatically activated neurocognitive processes gain in relative influence on substance use behavior, while the influence of cognitive control or reflective processes weakens. There is evidence that a variety of implicit cognitive processes, such as attentional bias, bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 110 publications
(179 reference statements)
2
40
0
Order By: Relevance
“…Therefore, these findings support the proposal of the dual-process model [13], suggesting that inhibitory control is poorer for the processing of specific affective stimuli (i.e., alcoholrelated in binge drinking) due to an interaction between an over-reactivity when processing affective or appetitive cues and a reduced executive control ability. Indeed, this view appears dominant in the literature and has also been proposed to explain binge drinking habits in young people [54,55]. Besides, the behavioral adjustment after feedback appears correctly performed in BD, which is also in line with previous electrophysiological results [33].…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, these findings support the proposal of the dual-process model [13], suggesting that inhibitory control is poorer for the processing of specific affective stimuli (i.e., alcoholrelated in binge drinking) due to an interaction between an over-reactivity when processing affective or appetitive cues and a reduced executive control ability. Indeed, this view appears dominant in the literature and has also been proposed to explain binge drinking habits in young people [54,55]. Besides, the behavioral adjustment after feedback appears correctly performed in BD, which is also in line with previous electrophysiological results [33].…”
Section: Discussionsupporting
confidence: 82%
“…Because PSU is associated with deficits in attentional orienting and control (e.g., difficulty regulating bias toward drug cues) and decision making (e.g., choosing whether or not to use substances; Field & Cox, 2008;Goldstein & Volkow, 2011;Koob & Volkow, 2010;Wiers, Boelema, Nikolaou, & Gladwin, 2015), individual differences in midfrontal theta, RTV, and parietal delta may be promising neurophysiological correlates of PSU. As parietal delta relates more strongly to the P3 than midfrontal theta (Bachman & Bernat, 2018;Karakas et al, 2000a), it is likely that theta, not delta, may account for variance in PSU separate from P3AR.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in young adults and adolescents have demonstrated that cognitive biases are associated with concurrent drinking (Field et al, 2007(Field et al, , 2008(Field et al, , 2011 and predictive of prospective drinking (Peeters et al, 2012(Peeters et al, , 2013; for a review, see Wiers et al, 2015). Further studies suggest that the link between cognitive biases and substance use is strongest when executive functions are weak Peeters et al, 2012Peeters et al, , 2013Thush et al, 2008;Van Hemel-Ruiter et al, 2014).…”
mentioning
confidence: 99%